The Application of Cooperative Learning in English Reading in Secondary School: A Case Study in Mainland China - Yuheng, Huang; Fengmei, Zou; Yiyu, Liao; Mengyi, Zhang; Xinyuan, Li (Interdisciplinary Issues in Education, 2024)
This paper explores the role of cooperative learning approach to English reading among secondary level students in China. As English as a foreign language is a part of school curriculum, developing students’ reading skills is essential to achieve the curricular goals. Since reading is challenging skill for non-native speakers, which is evident from the condition that despite teachers investing a lot of time in developing students’ reading skills, the level of improvement is not satisfactory. In the changed context of teaching and learning of English, cooperative learning has gradually become one of the most popular learning strategies in recent years as it encourages teachers and students to engage in complementing each other in learning, which greatly promotes learning interest and mobility, and also can be more conducive to teachers and students to break through the bottleneck of English reading. Two major questions raised were: a) Whether the cooperative learning affect students’ English reading ability? b) How does the cooperation affect students’ learning motivation in English reading? To respond to these questions, in this study, the data were gathered through an experiment conducted in grade eight that involved students in cooperative learning to develop their English reading. The results of the study indicated that cooperative learning improved students’ reading ability, enhanced their motivation and improved students’ learning enthusiasm. This implies that English as foreign language learning contexts should prioritise students’ engagement in cooperative learning.